PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE (ETH) DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 1 LEMBAH MELINTANG KABUPATEN PASAMAN BARAT - Sanusi, Ahmad; Zulfaneti, Zulfaneti; Yunita, Alfi (Pendidikan Matematika, 2013)
Everyone Is A Teacher Here (ETH) is a learning strategy that enables students to be expected to increase students understanding of the concept of SMAN 1 Lembah Melintang are low. The purpose of this research was to find out whether the students understanding of mathematical concept by applying active learning strategy ETH type it joined handout was better than applying conventional learning. Thish research is experimental research. The research population was X grade students of SMAN 1 Lembah Melintang West Pasaman district and samples were X3 as experimental class, X6 as control class. The instrument which was used in this research was essay test with index of reliability = 0,96. Based on the result of data analysis concerning with studentâs understanding of mathematical concept to both of classes. It was found that the mean score of experimental class = 76,10 and the mean score of control class = 63,53. The hypothesis testing shown that tcalculated =3.84 is low than t(0,95)(75) = 1,67, it could be concluded that the hypothesis was accepted. In other word the studentâs understanding of mathematical concept by applying active learning strategy ETH type it joined handout was better than conventional learning at confidence interval 95%.